DEPENDENCE OF THE ACTIVITY OF THE SYSTEM OF OXIDATIVE STRESS – ANTIOXIDANT PROTECTION ON INSULIN RESISTANCE IN PATIENTS WITH ESSENTIAL HYPERTENSION AND OBESITY - V. Psarova (Eastern Ukrainian Medical Journal, 2019)
Relevance. The activation of free radical oxidative processes and the development of oxidative stress is one of the most important pathogenetic mechanisms of cardiovascular diseases. Active forms of oxygen can change cellular infiltration of vessels and endothelial function, having an impact on a functional condition of the adhesive molecules intercellular adhesion molecule-1 and vascular cell adhesion molecule-1. Under condition of insulin resistance (IR), the balance in the system of oxidative stress – antioxidant protection is disturbed, the result of which is insufficient resistance to the damaging effect of the LPO products. The aim of the study was to assess the dependence of the activity of the system of oxidative stress – antioxidant protection on insulin resistance (IR) in patients with comorbidity of arterial hypertension and obesity. We examined 200 patients with hypertension and class I–II obesity. The patients were divided into two groups depending on IR: the first group included 80 patients without IR and the second group – 120 patients with IR. As the result of the study, it was established that the presence of IR affects the activity of the system of oxidative stress – antioxidant protection in comorbidity of hypertension and obesity. In the presence of IR, patients with hypertension and concomitant obesity have significantly higher levels of indicators of the system of oxidative stress (malondialdehyde (MDA) and diene conjugates (DC)) compared with patients without IR. In patients with comorbidity of hypertension and obesity, HOMA-IR directly correlated with the indicators of the oxidative stress system (MDA and DC) and inversely correlated with the indicator of total antioxidant protection. In hypertensive patients with obesity and no IR, an increase in HOMA-IR was associated with a decrease in total antioxidant protection, and in patients with IR, an increase in HOMA-IR was associated with an increase in MDA and DC, as well as a decrease in total antioxidant protection.